Traditionalism of Tolerance in Dayah System: A Reflective Note on the Biography of Abon Aziz Samalanga of Aceh - Nasution, Ismail Fahmi Arrauf; Miswari, Miswari; Haeba, Ilham Dwitama (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This article was aimed to analyze the values of tolerance and deradicalization in local wisdom through thebiography and contribution of Abon Aziz Samalanga. Using biographical approach, the author discussedAbon Aziz’s tolerance values through the traditional education method, political attitude and multiculturalvalues he was committed to. The article found that the procedure and in-depth exploration of traditionaleducation in dayah, day-to-day examples which were taught by involving students were tolerance andderadicalization materials very important to be learned again by students and society to prevent intoleranceand radical actions. Understanding the life of Abon Aziz Samalanga, students and the society will not onlypotentially be tolerant people but also deradicalization agents. This study contributes to Islamic educationand counter-radicalization research by demonstrating how traditional Islamic educational models can beeffective mechanisms for promoting peace and countering extremist ideologies. Furthermore, it offers aframework for applying biographical analysis in educational and social studies, highlighting the importanceof historical figures in shaping contemporary discourses on religious moderation.